2020
DOI: 10.3390/s20185130
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Effects on Chlorophyll Content Estimations with RGB Camera Mounted on a UAV Platform Using Machine-Learning Methods

Abstract: Timely monitoring and precise estimation of the leaf chlorophyll contents of maize are crucial for agricultural practices. The scale effects are very important as the calculated vegetation index (VI) were crucial for the quantitative remote sensing. In this study, the scale effects were investigated by analyzing the linear relationships between VI calculated from red–green–blue (RGB) images from unmanned aerial vehicles (UAV) and ground leaf chlorophyll contents of maize measured using SPAD-502. The scale impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 84 publications
1
30
0
2
Order By: Relevance
“…Linear relationships were employed in this study to characterize the response patterns of vegetation phenology and phenological climate sensitivity to nighttime light data; however, the complex nonlinear relationships between urbanization, climate factors, and phenology could not be excluded. Recent studies reported that machine learning methods such as support vector machines and random forests have achieved significant results in fitting climate factors to phenology, and it showed better performance than the linear method in the prediction of phenology [67][68][69][70], thereby provides new insights into the relationship between phenology and environmental factors. Furthermore, the method of classifying regional nighttime light levels focuses on the urbanization intensity as the sole classification criterion, so does not reflect differences in the topography or vegetation type.…”
Section: Uncertainty and Insightsmentioning
confidence: 99%
“…Linear relationships were employed in this study to characterize the response patterns of vegetation phenology and phenological climate sensitivity to nighttime light data; however, the complex nonlinear relationships between urbanization, climate factors, and phenology could not be excluded. Recent studies reported that machine learning methods such as support vector machines and random forests have achieved significant results in fitting climate factors to phenology, and it showed better performance than the linear method in the prediction of phenology [67][68][69][70], thereby provides new insights into the relationship between phenology and environmental factors. Furthermore, the method of classifying regional nighttime light levels focuses on the urbanization intensity as the sole classification criterion, so does not reflect differences in the topography or vegetation type.…”
Section: Uncertainty and Insightsmentioning
confidence: 99%
“…In 2013, Angela Lausch et al [ 16 ] studied the effects of different spatial resolutions on the NDVI to obtain a suitable scale. In 2019, Guo et al [ 17 ] investigated the scale effects by analyzing the linear relationships between VI calculated from red-green-blue (RGB) images from unmanned aerial vehicles (UAV) and ground leaf chlorophyll contents of maize measured using SPAD-502.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that images with different spatial resolutions have different effects on the accuracy of crop trait estimation. For example, Guo et al[51] used different flight altitudes to evaluate the impact of UAV images with different spatial resolutions on SPAD prediction. It was found that compared with images obtained with flight altitudes of 75m (2.1 cm/pixel), 100m (2.8 cm/pixel), and 125m (3.4 cm/pixel), imagery with a flying height of 50m (spatial resolution of 1.8 cm/pixel) can be used to estimate SPAD in leaves accurately.…”
mentioning
confidence: 99%